Implementasi Gerakan Literasi dalam Pembentukan Karakter Siswa di MI Muhammadiyah Losari Rawalo Banyumas - Meli Aprianti; Zakiyah Zakiyah (UM Purwokerto Press, 2022)
This study aims to examine how the implementation of literacy culture in the formation of student character at Madrasah Ibtidaiyah Muhammadiyah Losari Rawalo Banyumas for the 2020/2021 Academic Year. This research is a type of field research using a qualitative descriptive approach. The research subjects were the principal, fifth grade teacher, librarian, and fifth grade student. Data collection techniques were observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation, and conclusions. The results showed that the implementation of the School Literacy Movement (GLS) in building student character at MI Muhammadiyah Losari Rawalo Banyumas for the 2020/2021 academic year was carried out by habituation and growing interest in reading. The habituation and growth of reading interest is carried out by reading activities 15 minutes before the KBM (Teaching and Learning Activity), the existence of a routine schedule of library visits, the use of literacy corners in every corner of the classroom, and the provision of motivational walls from student work. The implementation of the School Literacy Movement (GLS) has a positive impact on the formation of student character, namely religious character, discipline, love of reading, and responsibility.